A1.4 Predictive factors for the eular response in ra patients with rituximab treatment. (31st January 2014) - Peltea, Alexandra; Mazilu, Diana; Gudu, Tania; Opris, Daniela; Ionescu, Ruxandra
Abstract : Background and Objective: The prediction of therapeutic response to Rituximab in Rheumatoid Arthritis is still an unmet need. This study aimed to identify useful and accessible predictive factors of non-responders to Rituximab ahead of time. Materials and Methods: 42 RA patients initiating Rituximab were included in this study and were prospectively followed for 18 months. The lymphocyte count (LyC), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF) and anti-CCP antibodies (ACPA) titres, disease duration and number of previous anti-TNFα drugs were assessed at baseline, at 6 and 18 months. The clinical response was evaluated using disease activity score (DAS28) based on ESR and European League Against Rheumatism (EULAR) response at 6 (ER6) and 18 months (ER18). Results: LyC at baseline is predictive for ER6 (F=4.597, p=0.041), but not for ER18, and the ER6 is predictive for ER18 (F=8.834, p=0.005). Also DAS28 at 6 months and the number of previous anti-TNFα drugs are predictive for ER18 (F=7.937, p=0.008, respectively F=4.356, p=0.044). Although we obtained a negative correlation between the ESR at 6 months and ER18 (p=0.002), the therapeutic response cannot be predicted based on ESR values. RF and ACPA titres, CRP values and the disease duration did not seem to correlate with the therapeutic response. Conclusions: The lymphocyte count at baseline represents a predictive factor for the EULAR response at 6 months. A better 6 months ER along with a lower DAS28 predict a better ER at 18 months of Rituximab treatment in RA patients.